ANALYSIS OF THE EFFECTS OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND SOCIAL CAPITAL ON PERFORMANCE US MSMEs THROUGH FINANCIAL INCLUSION INTERVENING VARIABLES (Case Study of MSMEs in Medan Marelan District) - Nia Dwi Syafira; Syahyunan; Rina Br. Bukit (CV. Radja Publika, 2024)
This study aims to analyze the influence of financial literacy, financial technology and social capital on the performance of MSMEs through financial inclusion as an intervening variable (case study of MSMEs in Medan Marelan District). Associative type of research. The population of this study were all culinary SMEs in Medan Marelan District. Sampling used the proportional stratified random sampling method of 170 respondents. Data processing uses Smart PLS 3. The research results show that financial literacy has a positive and significant effect on the performance of MSMEs, financial technology has a positive and significant effect on the performance of MSMEs, social capital has a positive and significant effect on the performance of MSMEs, financial inclusion has a positive and significant effect on the performance of MSMEs. The research results also state that financial literacy has a positive and significant effect on financial inclusion, financial technology has a positive and significant effect on financial inclusion, social capital has a positive and significant effect on financial inclusion. As well as the research results that financial inclusion mediates the influence of financial literacy on the performance of MSMEs, financial inclusion mediates the influence of financial technology on the performance of MSMEs and financial inclusion mediates the influence of social capital on the performance of MSMEs.